Gymnesigobius medits (Teleostei: Gobiidae), a new gobiid genus and species from the western Mediterranean slope bottoms - Kovačić, Marcelo; Ordines, Francesc; Ramirez-Amaro, Sergio; Schliewen, Ulrich K. (Zootaxa, 2019)
A new genus and species of goby, Gymnesigobius medits sp. nov., is described from the western Mediterranean slope bottoms at the Balearic Islands. The new goby belongs to the Gobius-lineage (Gobiinae). Examination of the single known specimen exhibits a unique combination of morphological characters which could not be fitted to any known genus. Gymnesigobius gen. nov. is morphologically distinguished from all other genera in the Gobius-lineage by the following combination of characters: chin without fold or barbels; mouth terminal with anterior tip above horizontal level of lower eye edge; predorsal area and first dorsal fin base naked; pelvic fin anterior membrane well developed; head with anterior oculoscapular and preopercular canals, posterior oculoscapular canal absent; pores of head canals enlarged, e.g. pores α and ρ larger or of about the same size as interspaces to pore β; six transverse suborbital rows of sensory papillae, four continuous suborbital rows in front of row b, fifth row divided in three parts but in front of row b, sixth row just as superior part above row b and below pore α; longitudinal suborbital row b barely reaching forward to the vertical from posterior edge of eye. A full description of the new genus and species is provided. The new species, collected at a depth of between 344 and 364 m (mean depth of 354 m), is one of very few gobiid species found at bathyal depths.